The Effect of Cardiopulmonary Resuscitation Education With SIKOMJARU Media on Compression Quality in Lay Community - Putri, Puja Dwi Febriana; Adhi, M. Hanif Prasetya; Endiyono, Endiyono; Ramdani, Meida Laely (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Cardiac arrest is an emergency condition requiring rapid treatment, and cardiopulmonary resuscitation skills are essential to improve the victim's chances of survival. Objective: This study aims to evaluate the effect of cardiopulmonary resuscitation education using SIKOMJARU media on compression quality in lay people in Kalisaleh village, Pemalang district. Methods: The method used was pre-experimental with a one group pretest and posttest design approach, involving 40 respondents from the local community. Before the intervention, respondents showed low understanding and skills in performing chest compressions. After receiving education and training using SIKOMJARU media, respondents practiced CPR techniques better. Results: The analysis results showed a significant improvement in compression quality, with a p value <0.05, indicating the effectiveness of SIKOMJARU media in improving respondents' knowledge and skills. Conclusion: The conclusion of this study is that cardiopulmonary resuscitation education with SIKOMJARU media can improve the community's ability to provide first aid to cardiac arrest victims, thus expected to contribute to increasing survival rates among these communities.